The role of oversight in foreign-national only prisons: counteracting the disapplication of rehabilitation - Mulgrew, Roisin (Springer, 2017)
In several European countries, prisons have been created solely to house foreign national prisoners without leave to remain. Contrary to contemporary international human rights law and standards on prison management, there seems to be a trend towards the disapplication of rehabilitative theory and practice for this group of prisoners. In particular, they do not seem to receive the same preparation for release and reintegrative support as other prisoners. This paper explores the role international standards and oversight bodies have in upholding rehabilitation as the foundational objective for prison management in foreign national only prisons. It outlines the changes to the prison estate, policy and regime that have resulted from the increasing focus on removal within both the prison and penal process. The consequences of the disapplication of rehabilitation for prisons, prison officers, prisoners and society itself are analysed before the paper moves to examine the role oversight bodies could and should play in the protection of the rights of this vulnerable category of prisoner and the primacy that should be accorded to rehabilitative theory and practice. It concludes by asking whether such standards and oversight have inverted the panopticon by placing the trigger for international reactions in the hands of prisoners and NGOs.